A inserç\~ao dos BRICS na África Austral - Caroline Chagas de Assis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Africa has had a renewed strategic importance in the 21st century. It is related to the uprise of new actor in international system that search markets and strategic partners. Whitin those new actors are Brazil, Russia, India and China (BRICs). In this context this paper seek to understand how BRICs introduce their selves in Southern Africa and how they set up commercially in this region, demonstrating the main strategies and mechanisms of approach. This paper is developed as part of the project "The Brazilian External Agenda to Africa: proposes and evaluation", requested for Ipea and developed during the year 2020. As a result of the research became evident that BRICs had a long history with Southern Africa, in spite of they are nowadays considered new players in the region. Despite BRICs are all together in the BRICS group, individually they have a different kind of insertion in Africa, what in some cases enables them to be complementary and in others strong competitors.
Keywords: N47; 330; BRICS; strategic partnership; Southern Africa